PERGESERAN REALITAS DAN HAK-HAK PEREMPUAN PERSPEKTIF KEADILAN JENDER DALAM RUMAH TANGGA: Studi Kasus Di Desa Cangaan Kecamatan Ujungpangkah Kabupaten Gresik - Faqihatin, Faqihatin (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2024)
Along with the rampant discussion about women’s issues, the modern Islamic discourse naturally intersects with matters relating to gender equality and women’s rights. This research is a type of field research, which is data collection is carried out in the field, such us in the society environment, social institutions and government agencies. This research is a kualitative research, which is a study that aims to explain a social phenomenon or an event. The data source is obtained from primary data, empirical data that obtained directly from household, while secondary data is supporting data comes from documents or literature related with modern Islamic perspective. The results obtained by researcher to measure whether shifting reality is really happening, it can be proved how women can claim their rights as people equal to men by suing devorce if they feel disadvantaged by men and also in the second point women also have the right for helping men or families to work.